The schooled society : the educational transformation of global culture - Baker, David, 1952 January 5- (Stanford University Press, 2014)
Only 150 years ago, the majority of the world's population was largely illiterate. Today, not only do most people over fifteen have basic reading and writing skills, but 20 percent of the population attends some form of higher education. What are the effects of such radical, large-scale change? David Baker argues that the education revolution has transformed our world into a schooled society-that is, a society that is actively created and defined by education. Drawing on neo-institutionalism, The Schooled Society shows how mass education interjects itself and its ideologies into culture at larg.